2017
DOI: 10.1136/bmj.j4651
|View full text |Cite
|
Sign up to set email alerts
|

Choice of implant combinations in total hip replacement: systematic review and network meta-analysis

Abstract: Objective To compare the survival of different implant combinations for primary total hip replacement (THR). Design Systematic review and network meta-analysis. Data sources Medline, Embase, The Cochrane Library, ClinicalTrials.gov, WHO International Clinical Trials Registry Platform, and the EU Clinical Trials Register. Review methods Published randomised controlled trials comparing different implant combinations. Implant combinations were defined by bearing surface materials (metal-on-polyethylene, ceramic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 31 publications
1
43
0
1
Order By: Relevance
“…The ever-improving survivorship of joint arthroplasties is evidence of the important continued innovation and improvement in implant design and surgical techniques, which has led to better implant fixation options, improved wear performance, and reduction in perioperative and postoperative complication rates [2,3]. The outcomes of novel implant design are not however always better than for existing implants [10,11]. Occasionally, innovation leads to unforeseen problems such as early implant failure, as exemplified by the DePuy articular surface replacement (ASR) hip implant, which failed because of higher than anticipated wear between the 2 metal bearing surfaces [12e14].…”
mentioning
confidence: 99%
“…The ever-improving survivorship of joint arthroplasties is evidence of the important continued innovation and improvement in implant design and surgical techniques, which has led to better implant fixation options, improved wear performance, and reduction in perioperative and postoperative complication rates [2,3]. The outcomes of novel implant design are not however always better than for existing implants [10,11]. Occasionally, innovation leads to unforeseen problems such as early implant failure, as exemplified by the DePuy articular surface replacement (ASR) hip implant, which failed because of higher than anticipated wear between the 2 metal bearing surfaces [12e14].…”
mentioning
confidence: 99%
“…Recently, the mechanism of osteolysis has been reported by various studies. It has been reported that wear debris could induce aseptic loosing and osteolysis [13][14][15] . Thus, in the present study, the clinical patients of hip arthroplasty with or without aseptic loosing were enrolled for studying the mechanism of osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, these constructs only account for 25% of THRs implanted in England and Wales in 2016 [7]. A recent network meta-analysis concluded that newer THR implant combinations were not superior to a reference implant combination (metal-on-polyethylene, small head, cemented), which may now be considered 'old technology' [12]. The same group have subsequently demonstrated the superior cost-effectiveness of this implant combination [13].…”
Section: Implant Design and Component Selectionmentioning
confidence: 99%